(untitled) (The Journal of Plant Protection Sciences, 2021)
A field trail was conducted at ’C’ Block farm, Kalyani for the control of leaf spot of Centella asiatica (Thankuni) caused by Alternaria sp. and target leaf spot of Rauvolfia serpentina (Sarpagandha) caused by Corynespora cassicola by spraying three fungicides (carbendazim at 0.1%, mancozeb at 0.025% and blitox at 0.25%) and four biocontrol agents 7 7 8 (Trichoderma viride at 10 cfu / ml, T. harzianum at 10 cfu / ml, Pseudomonas fluorescens at 10 cell / ml and Biomonas-a formulated product of P. fluorescens preparation at 0.15% for three times at an interval of 15 days. The results revealed that the lowest percent disease incidence (PDI) of leaf spot of Thankuni caused by Alternaria sp. and highest yield in number of leaves per sq.M was recorded where carbendazim was sprayed. The highest yield in fresh weight, dry weight of leaves, fresh weight and dry weight of 1000 leaves was recorded. Application of mancozeb resulted in the lowest PDI of target spot of Sarpagandha, increased the yield (both fresh weight and dry weight of the plant per sq.M) and increased the fresh weight and dry weight of plants.